Muscle Ring Finger 1 (MuRF1) and MuRF2 are Necessary but Functionally Redundant During Developmental Cardiac Growth and Regulate E2F1-Mediated Gene Expression In Vivo - Willis, Monte S. (2013)
AIMS: Muscle ring finger (MuRF) proteins have been implicated in the transmission of mechanical forces to nuclear cell signaling pathways through their association with the sarcomere. We recently reported that MuRF1, but not MurF2, regulates pathologic cardiac hypertrophy in vivo. This was surprising given that MuRF1 and MuRF2 interact with each other and many of the same sarcomeric proteins experimentally. METHODS AND RESULTS: Mice missing all four MuRF1 and MuRF2 alleles [MuRF1/MuRF2 double null (DN)] were born with a massive spontaneous hypertrophic cardiomyopathy and heart failure; mice that were null for one of the genes, but heterozygous for the other (i.e. MuRF1−/−//MuRF2+/− or MuRF1+/−//MuRF2−/−) were phenotypically identical to wild type mice. Microarray analysis of genes differentially expressed between MuRF1/MuRF2 DN, mice missing 3 of the four alleles, and wild type mice revealed a significant enrichment of genes regulated by the E2F transcription factor family. Over 85% of the differentially expressed genes had E2F promoter regions (E2f:DP; p<0.001). Western analysis of E2F revealed no differences between MuRF1/MuRF2 DN hearts and wild type hearts; however, chromatin IP studies revealed that MuRF1/MuRF2 DN hearts had significantly less binding of E2F1 in the promoter regions of genes previously defined to be regulated by E2F1 (p21, Brip1, and PDK4, p<0.01). CONCLUSION(S): These studies suggest that MuRF1 and MuRF2 play a redundant role in regulating developmental physiologic hypertrophy, by regulating E2F transcription factors essential for normal cardiac development by supporting E2F localization to the nucleus, but not through a process that degrades the transcription factor.